Pengaruh Budaya Organisasi dan Kepemimpinan Transformasional Terhadap Produktivitas Kerja Melalui Kepuasan Kerja Guru SMA Negeri di Kota Palangka Raya - Yeprina Prihatini Asie; Ahmad Suriansyah; Suhaimi Suhaimi (Universitas Negeri Malang, 2020)
Abstract: Teacher work productivity reflects their attitudes and skills in carrying out their duties, and is demonstrated through efforts in self-development, instructional innovation, and contributions to achieving school goals. This productivity is influenced by organizational culture, the transformational leadership of the school principal, and teacher job satisfaction. This study aims to analyze the direct and indirect effects of organizational culture, transformational leadership, and job satisfaction on the work productivity of public high school teachers in Palangka Raya City. The research employs a quantitative approach using a survey method. The study population consisted of 527 teachers from 10 public high schools in Palangka Raya, with a sample of 227 selected using proportional random sampling. Data were collected through a questionnaire that had been tested for validity and reliability. The data were analyzed using descriptive analysis, classical assumption tests, hypothesis testing through path analysis with multiple regression, and the Sobel test. The results of the study show that: (1) there is a direct influence of organizational culture, job satisfaction, and transformational leadership on work productivity; (2) there is a direct influence of organizational culture and transformational leadership on job satisfaction; and (3) there is an indirect influence of organizational culture and transformational leadership on work productivity.Based on these findings, it is recommended that schools pay attention to the factors that can enhance teacher work productivity. Schools should continue to maintain organizational culture, transformational leadership, and teacher job satisfaction to ensure their ongoing positive impact on teacher productivity. Keywords: Work Productivity, Organizational Culture, Transformational Leadership, Job Satisfaction Abstrak: Produktivitas kerja guru mencerminkan sikap dan keterampilan dalam menjalankan tugas, serta ditunjukkan melalui upaya pengembangan diri, inovasi pembelajaran, dan kontribusi terhadap pencapaian tujuan sekolah. Produktivitas ini dipengaruhi oleh budaya organisasi, kepemimpinan transformasional kepala sekolah, serta kepuasan kerja guru. Penelitian bertujuan untuk menganalisis pengaruh langsung dan tidak langsung budaya organisasi, kepemimpinan transformasional, kepuasan kerja terhadap produktivitas kerja guru SMA Negeri di Kota Palangka Raya. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei. Populasi penelitian sebanyak 527 guru dari 10 SMA Negeri di Kota Palangka Raya dan diambil 227 dipilih menggunakan teknik proportional random sampling. Instrumen pengumpulan data yaitu angket yang telah dilakukan uji validitas dan reliabilitas. Analisis data berupa analisis deskriptif, uji asumsi klasik, pengujian hipotesis menggunakan analisis jalur dengan metode regresi berganda, dan uji sobel. Hasil penelitian menunjukkan bahwa: terdapat pengaruh langsung antara budaya organisasi, kepuasan kerja dan kepemimpinan transformasional terhadap produktivitas kerja; terdapat pengaruh langsung antara budaya organisasi dan kepemimpinan transformasional terhadap kepuasan kerja; terdapat pengaruh tidak langsung antara budaya organisasi dan kepemimpinan transformasional terhadap produktivitas kerja. Berdasarkan hasil penelitian, disarankan sekolah untuk dapat memperhatikan faktor-faktor yang dapat meningkatkan produktivitas kerja guru. Sekolah perlu tetap mempertahankan budaya organisasi, kepemimpinan transformasional dan kepuasan kerja guru agar tetap berdampak kepada produktivitas kerja guru. Kata kunci: Produktivitas Kerja, Budaya Organisasi, Kepemimpinan Transformasional, Kepuasan Kerja